Lone stars - Lupica, Mike (Puffin Books : Scholastic Inc., 2018)
When Coach Coop, a former star player for the Dallas Cowboys, starts exhibiting side effects from the many concussions he suffered while playing professionally, twelve-year-old wide receiver Clay Hollis becomes determined to help him get through the football season until Thanksgiving, when Coach plans to attend a ceremony honoring him and his former Super Bowl-winning teammates.